Study of the effect of tissue conductivity on electroporation - Hemzal, M.; Aubrecht, V. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper deals with two different dynamic models of electrical conductivity and a static model for electroporation. Those models were used to calculate electric field distribution in the tissue, the current and the volume of the tissue that will be subjected to electroporation. The results are than compared to the experimental model. Improved model can be used to better predict ablation zones.
Keywords: biliary stent; electrical conductivity; electroporation; FEM; occlusion